Feminisme dan Teologinya: Interpretasi Hosea 4:6 di Era Postmodern - Wibowo, Darren Milano; Setyobekti, Andreas Budi (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2024)
The postmodern era is an era where the world experiences many renewals, especially in various abstract matters. The changes that occur are dominated by the fields of art, culture, philosophy, and economics. In the changes that occur, there is actually a deconstruction and restructuring of the previous mindset. Feminism is a movement that is growing and undergoing rapid transformation in this postmodern era. In some ways, this movement is quite contrary to the Word of God. So that in the end it pollutes the true knowledge as written in Hosea 4:6. As a result, the church now has challenges from the feminist movement and its theology in this postmodern era. The research work entitled "Feminism and Its Theology: Interpretation of Hosea 4:6 in the Postmodern Era" was written with the intention of increasing insight into the body of Christ and as a trigger for various further studies. In this study, the author uses a descriptive qualitative method based on literature to describe the profile and impact of feminism and its theology. In general, feminism has had a good impact on gender emancipation and has brought many changes to this world. But believer need to understand the real truth so that there is no misinterpretation of the Word of God. There are also various views of feminist theology that are not biblical. The hermeneutics of feminist theology tends to be inaccurate because it is not oriented to the Bible. But rather tends more towards the spirit and feelings of women that arise as a result of social suffering.AbstrakEra postmodern adalah sebuah era dimana dunia banyak mengalami pembaharuan terutama dalam beragam hal abstrak. Perubahan yang terjadi didominasi oleh bidang seni, budaya, filsafat, dan ekonomi. Dalam perubahan yang berlangsung sebenarnya terjadi dekonstruksi dan restrukturalisme dari pola pikir terdahulunya. Feminisme adalah sebuah kegerakan yang bertumbuh dan mengalami transformasi dengan pesat di masa postmodern ini. Dalam beberapa hal gerakan ini cukup bertentangan dengan Firman Allah. Sehingga pada akhirnya mencemari pengetahuan yang benar sebagaimana tertulis dalam Hosea 4:6. Sebagai dampaknya gereja kini memiliki tantangan dari kegerakan feminisme dan teologinya di era postmodern ini. Adapun karya penelitian dengan judul “Feminisme dan Teologinya : Interpretasi Hosea 4:6 di Era Postmodern” ditulis dengan maksud untuk menambah wawasan dalam tubuh Kristus dan sebagai pemantik untuk berbagai penelitian lanjutan. Dalam penelitian ini penulis menggunakan metode kualitatif deskriptif berbasis literatur untuk menguraikan profil dan dampak dari feminis serta teologinya. Secara garis besar feminisme telah membawa dampak yang baik untuk emansipasi gender dan telah membawa banyak perubahan dalam dunia ini. Tetapi umat Tuhan perlu mengerti kebenaran sesungguhnya sehingga tidak terjadi kesalahan interpretasi terhadap Firman Allah. Terdapat pula beragam pandangan teologi feminisme yang tidak Alkitabiah. Hermeneutika dari teologi feminis cenderung tidak tepat karena tidak berorientasi kepada Alkitab. Melainkan lebih condong kepada semangat dan perasaan wanita yang timbul sebagai akibat penderitaan sosial.